Wnt and ß-Catenin signaling and skeletal muscle myogenesis in response to muscle damage and resistance exercise and training - Newmire, D.; Willoughby, D. S. (International Journal of Kinesiology & Sports Science, 2015)
The factors that regulate skeletal muscle hypertrophy in human adults in response to resistance training (RT) has largely focused on endogenous endocrine responses. However, the endocrine response to RT as having an obligatory role in muscle hypertrophy has come under scrutiny, as other mechanisms and pathways seem to also be involved in up-regulating muscle protein synthesis (MPS). Skeletal muscle myogenesis is a multifactorial process of tissue growth and repair in response to resistance training is regulated by many factors. As a result, satellite cell-fused myogenesis is a possible factor in skeletal muscle regeneration and hypertrophy in response to RT. The Wnt family ligands interact with various receptors and activate different downstream signaling pathways and have been classified as either canonical (ß-catenin dependent) or non-canonical (ß-catenin independent). Wnt is secreted from numerous tissues in a paracrine fashion. The Wnt/ß-catenin signaling pathway is a highly-regulated and intricate pathway that is essential to skeletal muscle myogenesis. The canonical Wnt/ß-catenin pathway may influence satellite cells to myogenic commitment, differentiation, and fusion into muscle fibers in response to injury or trauma, self-renewal, and normal basal turnover. The current literature has shown that, in response mechanical overload from acute resistance exercise and chronic resistance training, that the Wnt/ß-catenin signaling pathway is stimulated which may actuate the process of muscle repair and hypertrophy in response to exercise-induced muscle damage. The purpose of this review is to elaborate on the Wnt/ß-catenin signaling pathway, the current literature investigating the relationship of the Wnt/ß-catenin pathway and its effects on myogenesis is response to muscle damage and resistance exercise and training.